2019
DOI: 10.3390/nano9040553
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Porous Carbon Derived from Sichuan Pepper for High-Performance Symmetric Supercapacitor with Decent Rate Capability and Cycling Stability

Abstract: Hierarchical micro-mesoporous carbon (denoted as HPC-2 in this study) was synthesized by pre-carbonization of biomass Sichuan pepper followed by KOH activation. It possessed well-developed porosity with the specific surface area of 1823.1 m2 g−1 and pore volume of 0.906 cm3 g−1, and exhibited impressive supercapacitive behaviors. For example, the largest specific capacitance of HPC-2 was tested to be ca. 171 F g−1 in a three-electrode setup with outstanding rate capability and stable electrochemical property, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…Most notably, the amorphous carbon is more active to the Boudouard reaction compared with graphite. Consequently, the calculated I D / I G value of the pepper straw char is 0.98, which is close to the result of 0.94 in the previous literature, suggesting that the pepper straw can be considered as a good fuel for the microtubular DC‐SOFCs.…”
Section: Resultssupporting
confidence: 87%
“…Most notably, the amorphous carbon is more active to the Boudouard reaction compared with graphite. Consequently, the calculated I D / I G value of the pepper straw char is 0.98, which is close to the result of 0.94 in the previous literature, suggesting that the pepper straw can be considered as a good fuel for the microtubular DC‐SOFCs.…”
Section: Resultssupporting
confidence: 87%
“…The CV profiles were tested at a constant scan rate of 30 mV/s within various ranges of voltage (see Figure S3). The peak tail, which appears as a consequence of an undesirable oxygen evolution reaction-induced peak in the CV profiles when the voltage is broadened to 1.5 V or higher, indicates that the maximum working voltage of the ASC should be around 1.2 V. Such a phenomenon was explained in a similar way in the previous literatures [52,53,54]. For example, Xu et al reported that the optimized operating voltage range of the ZIF-LDH/GO//ZIF-C/G device was 0–1.6 V in order to avoid the oxygen evolution reaction at 1.6–1.8 V [55].…”
Section: Resultssupporting
confidence: 71%
“…The CV curves remain closely quasi-rectangular without apparent distortion even at a scan rate of 100 mV/s. As the scan rate enhances from 5-100 mV/s, the quasirectangular shape is well maintained, implying the EDLC capacitive behaviour of electrode material and speedy diffusion of electrolyte ions within the electrode 64,65 .…”
Section: Morphology Of Bioelectrode Was Analysed By Sem Images Figurmentioning
confidence: 96%